3D printing of Fe3O4 functionalized graphene-polymer (FGP) composite microarchitectures. (15th October 2020) - Wajahat, Muhammad; Kim, Jung Hyun; Ahn, Jinhyuck; Lee, Sanghyeon; Bae, Jongcheon; Pyo, Jaeyeon; Seol, Seung Kwon
Abstract: Magnetic graphene composite comprising graphene sheets decorated with magnetite nanoparticles (NPs) is an important material with numerous successful and potential applications in electronics, chemistry, physics, and bio-medicine. The further use of this material relies on the development of an appropriate patterning method for the production of two-dimensional (2D) and three-dimensional (3D) magnetic graphene composite objects. This study presents a simple and effective strategy to fabricate 2D and 3D micropatterns of Fe3 O4 functionalized graphene-polymer (FGP) nanocomposite using extrusion-based 3D printing with a highly loaded FGP nanocomposite ink. The ink consisted of Fe3 O4 nanoparticles (NPs), graphene microflakes (GMFs), and hydroxypropyl cellulose (HPC), and was stable and suitable for 3D printing of FGP objects. Various FGP 3D microarchitectures, including a grid, honeycomb, pyramid, and square, were successfully printed using the layer-by-layer (LbL) printing approach. The printed objects exhibited a conductivity of ∼580 S m −1 and magnetic property of 15.8 emu g −1 . Successful demonstrations of electronic devices such as a magnet-guided car, a magnetic switch, and a 3D grid for electromagnetic interference (EMI) shielding are also described herein. This 3D printing approach was effective for the 2D and 3D patterning of functional nanocomposites and shows promise for advanced printed electronic applications. Graphical abstract: Image 1